2016
DOI: 10.29050/harranziraat.259108
|View full text |Cite
|
Sign up to set email alerts
|

Siverek Yöresinde Yetiştirilen Kızıl Banki ve Bastık Kabarcık Üzüm Çeşitlerinin Organik Asit ve Şeker İçeriklerinin Belirlenmesi Üzerine Bir Araştırma

Abstract: saptanmıştır. Üzümlerde yüksek oranda bulunan şekerler fruktoz ve glukoz iken tartarik asitin üzümde baskın olduğu ve bunu malik asitin takip ettiği, fumarik asitin ise eser miktarda bulunduğu görülmüştür.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…The fact that the color values of honey from different harvest years differ and there is no difference between proline and Brix values means that honey color cannot be used as the sole quality criterion. Regarding the connection between honey quality and color properties, Polat (2007) reports that the mineral content is higher in dark honeys. Haroun (2006) found that there was a signi cant negative correlation between L value and total phenolic and antioxidant content in honey with rates of 60.6% and 46.3%, respectively.…”
Section: Correlation Analysismentioning
confidence: 99%
“…The fact that the color values of honey from different harvest years differ and there is no difference between proline and Brix values means that honey color cannot be used as the sole quality criterion. Regarding the connection between honey quality and color properties, Polat (2007) reports that the mineral content is higher in dark honeys. Haroun (2006) found that there was a signi cant negative correlation between L value and total phenolic and antioxidant content in honey with rates of 60.6% and 46.3%, respectively.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Ayrıca bölgenin ekolojisi ve kültürel uygulamalarında oldukça etkili olabileceği düşünülmektedir. Aynı zamanda sıcaklık şekerin parçalanmasının daha hızlı ve titrasyon asitliği miktarının düşük düzeyde olması üzerine etkili olabilmektedir (Polat, 2016).…”
Section: Antioksidan Aktivite Tayiniunclassified
“…Doğan ve ark., (2018), Kabarcık çeşidi üzümlerinde farklı olgunluk dönemlerinde toplam fenol düzeyinin 1058.4 mg gallik asit g-¹ ta ile 2786.1 mg gallik asit g-¹ ta arasında değiştiğini kaydetmişlerdir. Polat (2016), Kabarcık üzüm çeşidinde toplam fenol düzeyini tane kabuğunda ortalama 0.167 g kg -1 , tane etinde 0.098 g kg -1 , çekirdekte ise, 0.542 g kg -1 ; Bastık Kabarcık çeşidi fenol kapsamını ise sırasıyla; 0.504 g kg -1 , 0.138 g kg -1 , 0.590 g kg -1 olarak belirlemiştir. Gündeşli ve ark.…”
Section: Antioksidan Aktivite Tayiniunclassified
See 1 more Smart Citation
“…For commercial purposes, corn syrups are subdivided into four types based on dextrose equivalent; 20-38 Dextrose Equivalent (DE), 38-58 DE, 58-73 DE and 73 DE or above (Blanchard, 1992). Sugar spectrum is determined by using HPLC (Polat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%